2016
DOI: 10.1590/1807-1929/agriambi.v20n5p434-440
|View full text |Cite
|
Sign up to set email alerts
|

Quantum efficiency of photosystem II and production of orange under salt stress and nitrogen fertilization

Abstract: A B S T R A C TThis study aimed to evaluate the salt tolerance of 'Mimo do Céu' orange grafted onto three rootstocks using physiological parameters such as maximum quantum efficiency of photosystem II (PSII) and the production of fruits. It also evaluated the effectiveness of increased nitrogen (N) fertilization in reducing the effects of salt stress. Two concomitant experiments were carried out under controlled conditions, using drainage lysimeters. The Experiment I evaluated the effects of the application of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
1
3
0
1
Order By: Relevance
“…photochemical efficiency in energy transfer from P680 to the electron transport chain(Lin et al, 2013). A similar fluorescence increase trend due to N fertilisation was observed bySousa et al (2016) in orange (Citrus spp. ), whereas Figueiredo et al (2019) evaluated the chlorophyll efficiency in sugar apple seedlings 60 days after sowing and observed no significant influence of N fertilisation.…”
supporting
confidence: 74%
“…photochemical efficiency in energy transfer from P680 to the electron transport chain(Lin et al, 2013). A similar fluorescence increase trend due to N fertilisation was observed bySousa et al (2016) in orange (Citrus spp. ), whereas Figueiredo et al (2019) evaluated the chlorophyll efficiency in sugar apple seedlings 60 days after sowing and observed no significant influence of N fertilisation.…”
supporting
confidence: 74%
“…The results investigation of Peña-Olmos et al (2013) showed that toxicity caused by an excess of iron induced an increased level of stress in the broccoli plants, causing decreased of the value of photosystem II's (PSII) maximum quantum yield (Fv/Fm). The maximum quantum efficiency of photosystem II was inhibited in citrus plants under saline stress (Sousa J.R.M., et al, 2016). In investigations Jia M. et al ( 2019) were shown, that the Fv/Fm of wheat leaves was tended to increase with increasing N application.…”
Section: Resultsmentioning
confidence: 97%
“…The Fv/Fm ratio showed a quadratic behavior, with a maximum point (0.802) reached at 88% of the recommended P rate, which represents an increase of 3.11% relative to that seen in plants subjected to 40% of the recommended rate (Figure 5D). There are reports that plants under no stress show quantum efficiency of photosystem II (Fv/Fm) in the range of 0.75 to 0.85 and that Fv/Fm values below or above this range reflect photoinhibitory damage to the reaction centers of photosystem II (Cruz, Cruz, Ferreira, Castro, & Almeida, 2014;Freire, Dias, Cavalcante, Fernandes, & Lima, 2014;Sousa et al, 2016;Guidi, Lo Piccolo, & Landi, 2019). Although the lowest value for Fv/Fm (0.776) was obtained in plants grown under 40% P 2 O 5 (Figure 5D), it must be considered that there was no photochemical damage, as it is within the range established by the abovementioned authors.…”
Section: Resultsmentioning
confidence: 99%